Enantioresolution of Chiral Derivatives of Xanthones on Different Types of Liquid Chromatography Stationary Phases: A Comparative Study - Fernandes, Carla; Pinto, Madalena; Elizabeth Tiritan, Maria (Current Chromatography, 2014)
Since the development of chiral stationary phases (CSPs), liquid chromatography has emerged as one of the most useful methods for analyses and preparation of enantiomerically pure bioactive compounds. However, the key for success of enantioseparation lies in the first place in the choice of a suitable CSP having enantioselectivity for the target enantiomers. Thus, this work describes a comparative study of resolution of seven chiral derivatives of xanthones (CDXs) on nine CSPs of different nature (four macrocyclic antibiotics, two Pirkle-type and three polysaccharide-based), under multimodal elution conditions. The polysaccharide-based CSPs have proved to be most suitable to separate this group of compounds, since all the CDXs were enantioseparated with excellent enantioselectivity and resolution. Six of the seven CDXs were separated on macrocyclic antibiotic-based CSPs, however with low enantioresolution. The Pirkle-type CSPs exhibited specificity on chiral discrimination behavior, presenting very high enantioselectivity for CDXs with aromatic group linked to the chiral moiety. This comparative study provides valuable information in the field of enantioresolution, and constitutes a useful background for subsequent studies of this important class of compounds.
Keywords: chirobiotic T